A new method to assess the influence of textiles properties on human thermophysiology. Part I: Thermal resistance. Issue 2 (20th April 2015) - Annaheim, Simon; Wang, Li-chu; Psikuta, Agnieszka; Morrissey, Matthew Patrick; Camenzind, Martin Alois; Rossi, René Michel
Abstract : Purpose: – The purpose of this paper is to determine the validity and inter-/intra-laboratory repeatability of the first part of a novel, three-phase experimental procedure using a sweating Torso device. Design/methodology/approach: – Results from a method comparison study (comparison with the industry-standard sweating guarded hotplate method) and an inter-laboratory comparison study are presented. Findings: – A high correlation was observed for thermal resistance in the method comparison study ( r =0.97, p <0.01) as well as in the inter-laboratory comparison study ( r =0.99, p <0.01). Research limitations/implications: – The authors conclude that the first phase of the standardised procedure for the sweating Torso provides reliable data for the determination of the dry thermal resistance of single and multi-layer textiles, and is therefore suitable as standard method to be used by different laboratories with this type of device. Further work is required to validate the applicability of the method for textiles with high thermal resistance. Originality/value: – This study provides the first "round-robin" data for measuring thermal resistance using a Torso device. In future publications the authors will provide similar data examining the repeatability of measurements that quantify combined heat and mass transfer.